Variance salinity concentrations effects on survival, growth and feeding of common carp (Cyprinus carpio) fingerlings - Al-Faiz, Nawras A.; Jabir, Amer A.; Yesser, Abdul- Karim T. (Iraqi Journal of Aquaculture, 2022)
This study was conducted to determine the effect of direct transportation of the common carp (Cyprinus carpio) fingerlings to salt solution of 4, 6, 8 and 12 g / L concentrations from a control solution of 2.2 g / L on growth and nutrition. The high mortality 100 % occurs during the first 24 hours at 8 and 12 g / L solution respectively. No fish mortality occurred at the treatment of 4 and 6 g / L during the same period. Statistical analysis of final weight, weight increase, daily growth rate, specific growth rate and relative growth rate showed no significant differences (P>0.05) between treatment 4 g / L and the control, but the treatment of 6 g / L exhibited significant different (P<0.05) with the control. The values of food intake for the body weight reached 3.59, 3.01 and 2.39 % for the treatments control, 4 g / L and 6 g / L respectively, with significant difference (P<0.05).